Life cycles of coral-associated-viruses related to diffrent health states collected in Hang Rai - Ninh Thuan, Vietnam - Hanh, Nguyen Kim; Mien, Pham Thi; Hai, Doan Nhu (Academia Journal of Biology, 2018)
In recent years, coral associated viruses could play primal role in protecting coral health, yet their ecological traits are poorly investigated. In this study, the abundance and life cycles (lysogeny and lytic) of viruses associated with contrasted coral health states (healthy and bleached) were studied and compared. In addition, the density of bacteria and Symbiodium were also be determined by epifluorescence microscopy. The results showed that viral abundance increased 1.2 times and bacterial abundance decreased 0.6 times in healthy corals compared to bleached ones. The number of Symbiodinium significantly reduced 5.6 times in bleached corals compared to healthy corals. One of the most important results in this study was the coexistence of the both lysogenic and lytic viruses in healthy coral. The fraction of lysogenic bacteria was 2 times higher in healthy corals than in bleached ones. Healthy corals carried 3.5-fold more viral production than the diseased ones. Overall, the results showed that, in healthy state, corals might be a favorable environment for viral infection, promoting the development of both temperate and virulent phages. This coexistence might be crucial for coral viability through the complex links with their coral-associated bacterial hosts